Implikasi Al-Qur’an Surat Ash-Shaffat Ayat 102 Terhadap Interaksi Edukatif Antara Pendidik Dan Peserta Didik (Kajian Ilmu Pendidikan Islam) - Fauziah, Hapsah; Abdussalam, Asep Muharrom (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
The Qur'an implicitly contains stories related to educational elements, particularly the educative interactions depicted in the story of Prophet Ibrahim (Abraham) and Prophet Ismail (Ishmael) in Surah Ash-Shaffat, verse 102. There are wisdoms and lessons that can be derived for educators in fostering educative interactions between educators and learners. An interaction can be considered educational if it involves educational objectives, educators, learners, content, and methods. The objectives of this research are to: (1) Understand educative interactions according to Islamic educational principles; (2) Explore the educative interaction between educators and learners in the Qur'an, specifically in Surah Ash-Shaffat, verse 102; (3) Identify the implications of Surah Ash-Shaffat, verse 102 on educative interactions between educators and learners. This qualitative research utilizes library research with a thematic (Maudu’iy) approach, using primary data from the Qur'an, specifically Surah Ash-Shaffat, verse 102. Secondary sources include exegeses (Tafsir), books, scholarly journals, and relevant articles. Data analysis employs content analysis methods. The findings reveal that educative interactions in Surah Ash-Shaffat, verse 102 emphasize educational values such as Prophet Ibrahim's democratic attitude, dialogic democratic methods, Ismail's obedience to his father as an educator, and obedience to Allah's commandments. The implications highlight components or aspects that form educative interactions derived from Surah Ash-Shaffat, verse 102, offering wisdom on how educative interactions between educators and learners can align with guidance in the Qur'an, Surah Ash-Shaffat, verse 102. Keywords: Ash-Shaffat verse 102, Islamic Educational Science, educative interaction